OPTIMALISASI MANAJEMEN KEPENGURUSAN MASJID DALAM UPAYA MENINGKATKAN KUALITAS IBADAH JAMA'AH MASJID - Muthia Dewi; Sri Rezki Maulina Azmi; Krisma Yogi Nopiana (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2023)
Abstract: Mosques are places of worship, education, community development, Islamic da'wah and culture, cadre formation and community unity. To optimize the role and function of the mosque, namely by making the mosque apart from being a place of worship, it is also a place for developing people. In this Abdimas, the author makes the Ma'shum Mosque the object of research. In this Abdimas, the author explains how mosque administrators implement management functions in various da'wah activities. The method used in Abdimas is a method of outreach to the community around the mosque which aims to implement the mosque management function in the implementation of da'wah implemented by the mosque, this is carried out in the context of achieving the goals and also efforts to prosper the mosque. After holding this counseling, it shows that the implementation of the mosque management function in the implementation of da'wah implemented by the Al-Ma'shum mosque is going well because in order to carry out the previous work program the administrators or takmir have prepared and planned the steps that will be carried out, this is carried out in order to achieve the goals and also efforts to prosper the mosque. This is proven by the activities that are always busy with the congregation. Keywords: Management; Quality of WorshipAbstrak: Masjid merupakan tempat ibadah, pendidikan, pengembangan masyarakat, dakwah dan kebudayaan Islam, pembentukan kader dan persatuan umat. Untuk mengoptimalkan peran dan fungsi masjid yaitu dengan menjadikan masjid selain sebagai tempat ibadah juga sebagai tempat pembinaan umat. Dalam Abdimas ini penulis menjadikan Masjid Mashum sebagai objek penelitian. Didalam Abdimas ini penulis memaparkan bagaimana pengurus masjid mengimplementasikan fungsi manajemen dalam berbagai kegiatan dakwah. Metode yang digunakan dalam Abdimas ini adalah metode penyuluhan kepada Masyarakat sekitar masjid yang bertujuan untuk implementasi fungsi manajemen masjid dalam pelaksanaan dakwah yang diterapkan oleh masjid, hal ini dilaksanakan dalam rangka pencapaian tujuan dan juga usaha pemakmuran masjid. Setelah diadakan penyuluhan ini, menunjukan bahwa implementasi fungsi manajemen masjid dalam pelaksanaan dakwah yang diterapkan oleh masjid Al-Mashum berjalan baik karena dalam rangka melaksanakan program kerja sebelumnya para pengurus atau takmir telah menyusun dan merencanakan langkah-langkah yang akan dilakukan, hal ini dilaksanakan dalam rangka pencapaian tujuan dan juga usaha pemakmuran masjid. Dibuktian dengan kegiatan-kegiatan yang berjalan selalu ramai oleh jamaah.Kata kunci: Manajemen Kepengurusan; Kualitas Ibadah